PENGARUH LARUTAN EKSTRAK DAUN SIRIH (Piper betle L.) 50% TERHADAP PELEPASAN ION METAL (Ni, Cr dan Fe) PADA BREKET ORTODONTIK - Marzuki Akbar J. Dundu; Grahita Aditya; Eko Hadianto (Odonto : Dental Journal, 2017)
Background: Orthodontic bracket is one of the components in a fixed orthodontic treatment. The influence of the oral cavity of an orthodontic bracket is a type IV hypersensitivity reaction due to corrosion on the bracket. The solution of extracts of betel leaf (Piper betle L.) of 50% which could affect corrosion. This study aimed to know the effect of betel leaf extract solution (piper betle L.) 50% against metal ion release.Method: The research method was “The Post Test Control Group Desain”, consists of four large groups respectively soaked with 6 units of brackets, consisting of a solution of betel leaf extract (piper betle L.) 50% (treatment), aquabidest (negative control), artificial saliva (negative control) and Naf (positive control) incubated for 7 days with a temperature of 370 C. Then ion measurement using the tool inductively coupled plasma – optical emission spectrophotometry (ICP-OES).Results: this study showed that the average release of ion the largest was on the solution of betel leaf extract (0.157167) then aquabides (0.086967), artificial saliva (0,08833) and sodium flouride (0.005533). Test results of Mann-Withney showed the presence of significant difference (p<0.05) release of ion Ni, Cr and Fe on four groups except among artificial saliva groups and sodium fluoride but the group that was soaked in a solution of betel leaf extract (piper betle L.) 50% occured a release of ion Ni, Cr and Fe higher. This is because the samples werestored in solution of betel leaf extract (Piper betle L.) of 50% which is a liquid electrolyte that can cause ion release.Conclusion: Betel leaf extract (piper betle L.) 50% is not effective to be used as an alternative to slow corrosive to metal ion (Ni, Cr and Fe) on a metal bracket.